2019
DOI: 10.1038/s41598-019-54182-2
|View full text |Cite
|
Sign up to set email alerts
|

Neddylation regulates excitatory synaptic transmission and plasticity

Abstract: Post-translational modifications, like phosphorylation, ubiquitylation, and sumoylation, have been shown to impact on synaptic neurotransmission by modifying pre- and postsynaptic proteins and therefore alter protein stability, localization, or protein-protein interactions. Previous studies showed that post-translational modifications are essential during the induction of synaptic plasticity, defined by a major reorganization of synaptic proteins. We demonstrated before that neddylation, a post-translational m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 27 publications
(47 reference statements)
1
8
0
Order By: Relevance
“…4b, c). Moreover, the expression of late-LTP is neddylation-sensitive and field excitatory postsynaptic potentiation slope values returned to baseline within three hours when the slices were treated with the NEDD8 inhibitor MLN4924 like reported previously [37] (Fig. 4d-f).…”
Section: Proteasomal Degradation Of Dnmt3a1 Requires Neddylationsupporting
confidence: 85%
“…4b, c). Moreover, the expression of late-LTP is neddylation-sensitive and field excitatory postsynaptic potentiation slope values returned to baseline within three hours when the slices were treated with the NEDD8 inhibitor MLN4924 like reported previously [37] (Fig. 4d-f).…”
Section: Proteasomal Degradation Of Dnmt3a1 Requires Neddylationsupporting
confidence: 85%
“…However, the function and regulatory machinery of neddylation in the brain remain largely unknown. Recent studies have demonstrated that inhibition of neddylation reduces synaptic maturation, basal synaptic transmission, presynaptic release probability, postsynaptic AMPA and NMDA currents, surface expression of AMPA receptors, synaptic plasticity (both long-term potentiation and long-term depression), and cognitive functions 14 , 17 , 31 , 32 . While PSD-95 was previously identified as a critical substrate of neddylation in postsynaptic spines, in this study, we demonstrated that presynaptic mGlu7 is a target of neddylation, and inhibition of neddylation reduces the clustering of mGlu7 to the presynaptic active zone and reduces the maturation of excitatory presynaptic terminals.…”
Section: Discussionmentioning
confidence: 99%
“…Neddylation enhances the activity of cullin-RING Ub ligases (CRLs), leading to the ubiquitination and subsequent degradation of their substrates, which are involved in multiple biological processes, including cell cycle progression 13 . Although NEDD8 was first identified in the brain, very few neddylation substrates, including PSD-95, cofilin/actin-depolymerizing factor (ADF), parkin, and PINK, have been identified in neurons 14 18 . A recent elegant study revealed that neddylation is essential for clustering of the dendrite scaffold protein PSD-95 and is necessary for dendritic spine stability and maturation 17 .…”
Section: Introductionmentioning
confidence: 99%
“…However, inhibition of the neddylation pathway does not enhance synaptic activity and strength as it would have been expected as a consequence of reduced synaptic ubiquitination. Instead, it destabilizes dendritic spines, affects synaptic transmission and plasticity, and impairs cognitive functions (Scudder and Patrick, 2015;Vogl et al, 2015;Brockmann et al, 2019), thus suggesting that neuronal neddylation targets other substrates relevant to synaptic function. In line with this, Vogl and colleagues elegantly demonstrated that PSD-95 is neddylated at K202 by MDM2 (Vogl et al, 2015), which also mediates PSD-95 ubiquitination ( Fig.…”
Section: Neddylationmentioning
confidence: 99%